International law and the reconceptualization of territorial boundaries - Castellino, Joshua, author.
1 online resource
Keywords: "This book critically analyzes the state-based regime of international law, eliciting its colonial and decolonial origins and proposing a new sub-regional basis for dealing with contemporary global challenges. Since 1648 public international law has taken many steps to maintain peace and establish a just order. The State is deemed central to each of these. Yet modern challenges, such as environmental mitigation, mass migration and need to stimulate economic growth, overwhelm the State. Could a regional approach to these questions, achieved in conjunction with strong sub-national local governance establish a more effective framework for systemic change? Drawing on a history of colonization and decolonization, while scrutinizing decisions made about the imposition of the State on the basis of colonial boundaries, this multidisciplinary work analyzes why current challenges are unlikely to be adequately addressed through existing governance structures. In response, it advocates a sub-regional, transnational approach, drawing on analyses of pre-colonial shared histories and contemporary population ethnographies unfettered by hegemonic boundary drawing. The book argues that collaboration across such frontiers in the face of climate and other challenges may offer more feasible approaches to the pursuit of peace than unquestioned maintenance of the state-based structures of inherited privilege. This book will appeal to scholars and others with interests in international law, international relations, and international politics, as well as in the history and politics of colonialism"--